(untitled) (GESTIÓN Y TENDENCIAS, 2023)
This article investigates the influence of legal quality and the rule of law on access to business financing in Latin American countries. Drawing on the contractual theory of the firm and the Law and Finance literature, the study compares economies in the region classified by institutional quality (high vs. low) using World Bank governance indicators and Enterprise Surveys data. The empirical results indicate that nations with stronger legal traditions and greater judicial efficiency display deeper credit markets, a higher share of investment financed by banks, and more extensive use of long-term debt. It concludes that reforms aimed at protecting creditor and investor rights are decisive in reducing credit constraints and fostering a stable environment for business development.